Educational disparities in disability-free life expectancy across Europe: A focus on the East-West gaps from a gender perspective - Donata Stonkute; Angelo Lorenti; Jeroen J.A. Spijker (Elsevier, 2023)
Education plays a crucial role in shaping the health outcomes of adults. This study examines the relationship between educational attainment and health across Europe. Using data from the Survey of Health, Ageing and Retirement in Europe (SHARE), we estimate educational inequalities in disability-free life expectancy (DFLE) by gender in seven Western European (2004-2019) and three Central and Eastern European (CEE) (2010-2019) countries. We exploit a novel approach that combines the Sullivan method and multivariate life tables to calculate DFLE using SHARE data. We find that educational differences in DFLE favoring the better-educated exist in both CEE and Western European countries, but also that the differences across countries are more pronounced among the low-educated. While the absolute gaps in DFLE between low- and high-educated individuals in CEE and Western European countries are similar, the educational disparities in DFLE impose a more significant burden on the CEE populations due to their overall lower life expectancy. Educational inequalities are larger among women than among men in CEE countries, while the results for Western European countries are mixed. Our findings further highlight the important role of the institutional context in mitigating or exacerbating educational inequalities in health.